Intracellular Motility of Intermediate Filaments - Leube, Rudolf E. (Cold Spring Harb Perspect Biol, 2017)
The establishment and continuous cell type–specific adaptation of cytoplasmic intermediate filament (IF) networks are linked to various types of IF motility. Motor protein–driven active transport, linkage to other cellular structures, diffusion of small soluble subunits, and intrinsic network elasticity all contribute to the motile behavior of IFs. These processes are subject to regulation by multiple signaling pathways. IF motility is thereby connected to and involved in many basic cellular processes guarding the maintenance of cell and tissue integrity. Disturbances of IF motility are linked to diseases that are characterized by cytoplasmic aggregates containing IF proteins together with other cellular components.